Effect of variety and seed rate of mungbean on weed suppression and yield under strip tillage system (Journal of the Bangladesh Agricultural University, 2016)
Mungbean can successfully be grown under strip tillage system if appropriate seeding rate can determine and adjust with machine. Due to high weed pressure in strip tillage system, selection of such mungbean varieties that have some potentialities to suppress weeds need to find out and moreover, determining optimum seed rate for different varieties could help to achieve best yield. Therefore, a study was conducted at Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during March-June, 2013 to study the effect of variety and seed rate on weed suppression and yield performance of mungbean under strip tillage system. The study comprised three mungbean varieties (BARI mung-6, BINA mung-5 and BINA mung-8) and five seed rates (20, 25, 30, 35 and 40 kg ha-1). The experiment was laid out in split-plot design with three replications. The study exposed that variety and seed rate had significant effect on plant population of mungbean, weed dry matter, number of pods plant-1, pod length, number of seeds pod-1, seed yield and stover yield of mungbean. The study results clearly found that weed population significantly reduced with increasing seeding rate of mungbean. Seeding of mungbean at 40 kg ha-1 and 35 kg ha-1 could successfully suppress weed under strip tillage system. Moreover, BINA mung-8 and BINA mung-5 had the more potentiality to suppress weeds compare to BARI mung-6. However, BINA mung-5 was found the superior among the three tested varieties that produced the highest seed yield from 35 kg ha-1 seed rate. In case of BARI mung-6 and BINA mung-8, maximum seed yield was also obtained from 35 kg ha-1 seed rate. Therefore, the study concluded that seeding of any of the three mungbean varieties at 35 kg ha-1 rate may help to obtain the satisfactory yield but the study suggest cultivation of BINA mung-5 at 35 kg ha-1 seeding rate under strip tillage system that will give not only the optimum seed yield but also provide good weed suppression.J. Bangladesh Agril. Univ. 14(1): 49-56, June 2016